Etnomatematika dalam Seni Geometri Islam: Integrasi Pola Ornamen pada Rancang Bangun Arsitektur Mesjid Taqwa Lhong Raya Banda Aceh - Teuku Ivan; Masdar Djamaludin; Mirza; Husnus Sawab; Safwan (Jurnal Serambi Engineering, 2025)
The Masjid Taqwa Lhong Raya mosque in Banda Aceh is an architectural masterpiece of Islamic design. Not only is it a place of worship, it also showcases a rich blend of art and mathematical symbolism. Situated on Jalan Sultan Malikul Saleh, the mosque's beauty lies in the ornamentation of its façade and the interior design, which harmoniously integrate elements of art, geometry, and Islamic architecture. This study uses a mixed-methods approach, combining qualitative and quantitative methods, to analyse the concept of ethnomathematics in the ornamentation of Masjid Taqwa Lhong Raya. Data were collected through interviews, literature reviews, and direct observation. The findings reveal that mathematical elements such as symmetry, proportion and geometric shapes, including triangles, circles and cubes, are applied harmoniously in the mosque's structure and ornamentation. These elements possess aesthetic and functional value, as well as containing symbolic meanings that reflect a fusion of local Acehnese culture and Middle Eastern influences. These findings make a significant contribution to interdisciplinary learning, particularly in architecture and mathematics.